Finding maximal closed substrings - Badkobeh, Golnaz; De Luca, Alessandro; Fici, Gabriele; Puglisi, Simon J. (Theoretical computer science, 2026)
A string is closed if it has length 1 or has a nonempty border without internal occurrences. In this paper, we introduce the notion of a maximal closed substring (MCS), which is an occurrence of a closed substring that cannot be extended to the left nor to the right by one character into a longer closed substring. MCSs with exponent at least 2 are commonly called runs; those with exponent smaller than 2, instead, are particular cases of maximal gapped repeats. We provide an algorithm that, given a string of length n, locates all MCSs the string contains in O(nlogn) time.